Sexuality as an incident. Analysis of homosexuality between mid-1956 and the end of 1980 from the journalistic view. - Rovira, Paula Sequeira (2020)
The following document is interested in analyzing some of the journalistic perceptions that existed in Costa Rica on homosexuality between 1965 and the end of 1980. To do this, several news that appeared in the newspaper La República were analyzed, in which homosexuality had almost an exclusively place in the accidents and crimes reports. Homosexual men were portrayed not only with female but, above all, with criminal characteristics. They were presented as dangerous beings for the judicial, political, moral, social and religious system. In fact, prison and the criminalization of the homosexual were necessary to produce this sexual identity. Marginally, general aspects of another character of the accidents and crimes reports such as the satyr will also be discussed, in order to show how the homosexual of the crimes reports was perceived as a more complex criminal than other sexual subjects of the same section.